Nghiên cứu tổng hợp, đặc trưng và hoạt tính xúc tác của vật liệu lai hóa vô cơ - hữu cơ SBA-15 chứa Cu và Fe - Nguyễn Thị Vương Hoàn; Ngô Thị Kỳ Xuân; Trần Thị Huỳnh Như Thanh; Bùi Thị Ly Na; Đặng Tuyết Phương; Nguyễn Hữu Phú (My University, 2010)
Nghiên cứu tổng hợp, đặc trưng và hoạt tính xúc tác của vật liệu lai hóa vô cơ - hữu cơ SBA-15 chứa Cu và Fe
Keywords: SBA-15